266 Administering an appeasing substance to beef calves at weaning to optimize welfare and productivity. (30th November 2020) - Schubach, Kelsey; Cooke, Reinaldo F; Brandão, Alice; Rett, Bruna; Ferreira, Vitor; Scatolin, Giovanna; Colombo, Eduardo; Daigle, Courtney L; Pohler, Ky G; Cappellozza, Bruno I
Abstract: This experiment evaluated the impacts of bovine appeasing substance (BAS) administration on performance, behavioral, and physiological responses of beef calves upon weaning. Eighty Angus-influenced calves (40 heifers, 40 steers) were weaned at 233 ± 2 d of age (d 0), ranked by age and body weight (BW), and assigned to receive BAS (Nutricorp, Araras, SP, Brazil; n = 40) or placebo (diethylene glycol monoethyl ether; CON; n = 40). Treatments (5 mL) were topically applied to the nuchal skin area of each animal. Within treatment, calves were allocated to 1 of 8 drylot pens (4 pens/treatment) and received a free-choice total mixed ration (TMR) from d 0 to 42, intake of which was assessed daily. On d 0, calves were fitted with a pedometer behind their right shoulder, and pedometer results were recorded weekly during the experiment (d 0 to 42) concurrently with full BW collection and temperament evaluation. Blood samples were collected on d 0, 3, 7, 14, 28, and 42, and hair samples were collected from the tail switch on d 0, 14, 28, and 42. Average daily gain from d 0 to 42 did not differ between treatments (P = 0.52), but was greater (P = 0.05) in BAS vs. CON calves from d 0 to 28. Intake of TMR was greater during the first week for BAS vs. CON calves (P = 0.05), and similar (P ≥ 0.44) from wk 2 to 6 (treatment × week; P = 0.08). Exit velocity was greater (P = 0.03) for CON vs. BAS calves on d 14 and tended (P = 0.08) to be greater for CON vs. BAS calves on d 7 (treatment × day; P = 0.04). Physical activity was greater for CON vs. BAS calves on d 1 (P < 0.01), but greater (P = 0.01) in BAS vs. CON on d 2 (treatment × day; P = 0.01). Mean plasma concentrations of haptoglobin were greater (P = 0.03) in CON vs. BAS calves during the experiment. Hair cortisol concentrations were greater (P = 0.0 5) in CON vs. BAS calves on d 14 (treatment × day interaction; P = 0.03). Results from this experiment indicate BAS calves habituated to their environment more rapidly through increased physical activity, which facilitated a lessened stress response associated with weaning, and accelerated adaptation to a novel environment. This was manifested through improved TMR intake and BW gain during the initial period of the experiment. Collectively, results suggest use of BAS as a strategy to improve calf welfare and productivity upon weaning.